Control of Volunteer Enlist Corn in Enlist E3 Soybean - R. Liu; I. Effertz; T. Lambert; V. Kumar (Kansas Agricultural Experiment Station Research Reports, 2021)
Recent development of Enlist corn allows the use of 2,4-D choline (Enlist One), glyphosate (Roundup PowerMax), glufosinate (Liberty), and aryloxyphenoxypropionate (FOPs) herbicides for controlling grass and broadleaf weeds. However, volunteer Enlist corn plants can cause infestation in subsequent Enlist E3 soybean (resistant to 2,4-D, glyphosate, and glufosinate) in areas where a corn-soybean rotation is commonly practiced. The main objective of this research was to determine the effectiveness of cyclohexanedione (DIMs) herbicides alone or in tank-mixtures with Enlist One for Enlist corn control in Enlist E3 soybean. A field study was conducted in the 2020 growing season at the Kansas State University Agricultural Research Center (KSUARC) near Hays, KS. Enlist corn hybrid DKC62-53 was planted at 17,420 seeds/a on May 13, 2020. Enlist E3 soybean variety P30T92E was planted at 152,000 seeds/a in a perpendicular direction to corn on May 20, 2020. Herbicide treatments, including clethodim (Select Max) and sethoxydim (Poast Plus) were tested alone or in tank-mixtures with Enlist One as early POST (EPOST, 8- to 12-inch tall corn), or late postemergence (POST) (12- to 30-inch tall corn). Results indicated that Select Max applied EPOST alone provided an excellent, season-long control (95 to 99%) and highest biomass reduction (up to 100%) of volunteer Enlist corn in Enlist E3 soybean. However, volunteer corn control was significantly reduced when Enlist One was tankmixed with Poast Plus. Volunteer corn control was low to moderate (50–85%) with all late postemergence (LPOST) programs tested. Soybean grain yield did not differ among EPOST treatments (39 to 44 bu/a), while grain yield was significantly lower ( 34 bu/a) for LPOST treatments. These results suggested that the EPOST application of Select Max and Poast Plus can effectively control volunteer Enlist corn infestation in Enlist E3soybean. However, adding Enlist One could compromise the efficacy of Poast Plus herbicide.
Keywords: Enlist One; Enlist soybean; Poast Plus; Select Max; volunteer corn